Prospective study of colposcopic screening of unhealthy cervix - Kannoujiya, Pushpa; Shrivastava, Arpita; Mala, Tariq Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The study was conducted to screen women who have abnormal vaginal discharge with Pap smear to do histopathological analysis of colposcopically directed biopsies. Methods: A prospective analytical study carried out in the department of obstetrics and gynaecology. The patients were randomly selected who fulfilled the selection criteria and was carried out to study the correlation of Pap smear and colposcopy in women with unhealthy cervix. Results: Among all patients 13% were between 20-29 years, 38% were between 30- 39%, 31% belonging to 40-49 years group and 18% was between 50-59%. Among 100 Women studied, 33% were illiterates, 55% had primary/high school education and 12% had Higher education Majority of the patients (68.7%) of CIN occurred in the age group of 30-49years, 41.7% with CIN were paragrvida 2, 43.8% with CIN were paragravida 3 and 18.6% were greater than paragravida 4 showing high incidence of CIN in multiparity.The incidence of CIN was found to be high among the lower income group 87.5%.The major presenting complains in the study patients were white discharge per vagina. Conclusions: Colposcopy was found to be useful in understanding the morphology of the cervical lesion, both of the neoplastic and nonneoplastic ones and was very helpful in planning their management. Cytology is an accepted method for screening for cervical cancer and the value of colposcopy has been recognized. Hence it may be better to utilize cervical cytology smear with colposcopy should be offered as a diagnostic method in all patients with unhealthy cervix.